Revitalisasi Birokrasi Pemerintah untuk Pelayanan Publik - Dr. Deddy Mulyadi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Bureaucracy revitalization and reform have been carried out for years. However, the result of this effort especially in improving public service has not been optimal yet. This paper attempts to clarify two aspects from the effort. First, it is important to explicate the revitalization and reform of bureaucracy from public administration point of view in the globalization context. It is assumed, for instance, that the efforts to revitalize and restructure the bureaucracy has only benefited the exclusive group of businessmen (conglomerates) in Jakarta, not the grassroot economy of people in the regions. Secondly, the paper tries to propose an effective public service as the indicator of the successful revitalization and bureaucracy reform. One of the crucial steps to improve public service is to downsize and simplify the structure of departments both in the central and local governments.